Interleukin-17 Links Inflammatory Cross-Talks Between Comorbid Psoriasis and Atherosclerosis - Wang, Yan; Zang, Jinxin; Liu, Chen; Yan, Zhongrui; Shi, Dongmei (Frontiers in Immunology, 2022)
Psoriasis is a chronic, systemic, immune-mediated inflammatory disorder that is associated with a significantly increased risk of cardiovascular disease (CVD). Studies have shown that psoriasis often coexists with atherosclerosis, a chronic inflammatory disease of large and medium-sized arteries, which is a major cause of CVD. Although the molecular mechanisms underlying this comorbidity are not fully understood, clinical studies have shown that when interleukin (IL)-17A inhibitors effectively improve psoriatic lesions, atherosclerotic symptoms are also ameliorated in patients with both psoriasis and atherosclerosis. Also, IL-17A levels are highly expressed in the psoriatic lesions and atherosclerotic plaques. These clinical observations implicit that IL-17A could be a crucial link for psoriasis and atherosclerosis and IL-17A-induced inflammatory responses are the major contribution to the pathogenesis of comorbid psoriasis and atherosclerosis. In this review, the current literature related to epidemiology, genetic predisposition, and inflammatory mechanisms of comorbidity of psoriasis and atherosclerosis is summarized. We focus on the immunopathological effects of IL-17A in both diseases. The goal of this review is to provide the theoretical base for future preventing or treating psoriasis patients with atherosclerosis comorbidity. The current evidence support the notion that treatments targeting IL-17 seem to be hold some promise to reduce cardiovascular risk in patients with psoriasis.